Stimulating smallholder tree planting – lessons from Africa and Asia - Nawir, A.A.; Kassa, H.; Sandewall, M.; Dore, D.; Campbell, Bruce M.; Ohlsson, B.; Bekele, M. (2007)
This article describes some different schemes through which smallholders participate in establishing and managing productive plantations. These reflect a continuum from management by tree growers themselves to private corporate initiatives, with government-initiated collaborative management in between. For each of these schemes, the article identifies key incentives – defined as “payments or services that increase the comparative advantage of forest plantations over other land use options and thus stimulate investments in plantation establishment and management” (Enters, Durst and Brown, 2003) – that can promote smallholder involvement in tree planting, although the strategies of course vary according to the country and the local conditions. The article highlights the importance of supportive policies and legislation, and clear, secure forest land tenure and management rights as enabling conditions for sustainable smallholder tree growing.